The impact of gradient variable temperature fermentation on the quality of cigar tobacco leaves - Zhang, Qianying; Huang, Yang; An, Hongyue; Yang, Shuanghong; Lei, Jinshan; Wang, Yue; Li, Pinhe; Zhang, Hongfei; Cai, Wen; Jia, Yun; Pang, Yongqiang; Li, Dongliang (Frontiers in Microbiology, 2024)
IntroductionIn order to enhance the quality of cigar tobacco leaves (CTLs), a gradient variable temperature fermentation approach was employed.MethodsThe temperature gradient demonstrated a gradual increase from low temperature (35 ± 2°C) to moderate temperature (45 ± 2°C), and then to high temperature (55 ± 2°C). Each temperature gradient underwent a 10-day fermentation process, resulting in a total duration of 30 days. Changes in sensory evaluation, chemical composition, and bacterial absolute quantitative structure and function were examined throughout the process of gradient variable temperature fermentation.ResultsCompared to constant temperature fermentation, gradient variable temperature fermentation improved the sensory quality of CTLs, reduced total sugar and cembrane degradation products, and increased the amino acid contents. It resulted in significant changes in bacterial quantity and function of CTLs, but had no significant effects on the richness and diversity of bacterial communities. The results of correlation analyses showed that sensory quality had significant correlation with chemical composition, which effected by predominant microbes. The gradient variable temperature fermentation process underwent a three-phase model to characterize the alterations of CTLs. Phase I (35°C) was the microbial stage, during which there was a significant decrease in both the total number and function of microorganisms. The dominant genera shifted from Acinetobacter to Staphylococcus and Corynebacterium, and with high reducing sugar, polyphenol compound and low sensory score. Phase II (45°C) marked a chemical stage, with an enhancement in sensory evaluation. A total of 17 chemicals significantly decreased and six increased, and the decline of microbial populations persisted. The enhanced relative abundances of four microecological hubs, namely Staphylococcus, Corynebacterium, Oceanobacillus, and Bacillus, had the potential to produce protease and lipase to the production of peptides, amino acids, and organic acid, catabolizing sugars and polyphenol compounds, through carbohydrate metabolism and amino acid metabolism, resulted an increase in sensory quality of CTLs. Phase III (55°C) indicated a relative mature stage with the highest score of sensory evaluation. Eight compositions from plamochromic pigments and polyphenol compounds exhibited gradual decreases, while relative contents of carbohydrate metabolism and amino acid metabolism increased.ConclusionThe gradient variable temperature fermentation had demonstrated a significant positive influence on the quality of CTL by providing optimal fermentation temperature for microbial growth, metabolism, and the generation of quality-related chemical compositions.